2021
DOI: 10.3389/fimmu.2021.664417
|View full text |Cite
|
Sign up to set email alerts
|

RBM39 Alters Phosphorylation of c-Jun and Binds to Viral RNA to Promote PRRSV Proliferation

Abstract: As transcriptional co-activator of AP-1/Jun, estrogen receptors and NF-κB, nuclear protein RBM39 also involves precursor mRNA (pre-mRNA) splicing. Porcine reproductive and respiratory syndrome virus (PRRSV) causes sow reproductive disorders and piglet respiratory diseases, which resulted in serious economic losses worldwide. In this study, the up-regulated expression of RBM39 and down-regulated of inflammatory cytokines (IFN-β, TNFα, NF-κB, IL-1β, IL-6) were determined in PRRSV-infected 3D4/21 cells, and accom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…RNA-binding motif protein 39 (RBM39) is a transcriptional coactivator of AP-1/Jun, an estrogen receptor, and NF-kappa B, and involves precursor mRNA splicing. RBM39 was shown to promote PRRSV infection by interacting with NSP4 to regulate c-Jun phosphorylation [ 38 ]. In addition, NSP4 can interact with F-actin and myosin IIA to complete the transmission and infection of PRRSV between cells [ 39 ].…”
Section: Nonstructural Proteinsmentioning
confidence: 99%
“…RNA-binding motif protein 39 (RBM39) is a transcriptional coactivator of AP-1/Jun, an estrogen receptor, and NF-kappa B, and involves precursor mRNA splicing. RBM39 was shown to promote PRRSV infection by interacting with NSP4 to regulate c-Jun phosphorylation [ 38 ]. In addition, NSP4 can interact with F-actin and myosin IIA to complete the transmission and infection of PRRSV between cells [ 39 ].…”
Section: Nonstructural Proteinsmentioning
confidence: 99%
“…Other strategies for evading the host immune system that are regulated by transcription factors TFDP Studies have found that some viruses can affect the process of the host cell cycle to provide a cell environment conducive to virus proliferation. It was found that TFDP2, a transcription factor significantly overexpressed in PRRSV-infected 3D4/21 cells, can positively regulate the expression of cyclin A, reduce the proportion of S-phase cells and promote the proliferation of PRRSV (Zhu et al, 2021). The reduction in the number of PRRSV cells in S phase was shown to be beneficial to PRRSV proliferation, possibly because the S phase provided fewer ribonucleotides for PRRSV RNA synthesis than the G0/G1 phase.…”
Section: Ap-mentioning
confidence: 99%
“…RNA binding motif protein 39 (RBM39) is a nuclear protein that is involved in precursor mRNA splicing. Studies have shown that PRRSV can significantly promote the expression of RBM39 in PRRSV-infected 3D4/21 cells (Song et al, 2021 ). The transcription factor RBM39 can evade the host immune system in the following ways: first, RBM39 alters the phosphorylation of the transcription factor c-Jun, and then inhibits the AP-1 pathway to promote virus differentiation; second, PRRSV infection causes RBM39 and c-Jun to migrate from the nucleus to the cytoplasm.…”
Section: The Role Of Transcription Factors In Prrsv Infectionmentioning
confidence: 99%
“…RNA‐binding motif (RBM) proteins are members of the family of RNA‐binding proteins (RBPs), which are present in all organisms and can bind single‐ or double‐stranded RNA and play important roles as post‐transcriptional regulators in regulating RNA metabolism and gene expression. 2 By binding RNA, RBPs aggregate in ribonucleoprotein complexes that determine the destiny and function of almost every cellular RNA molecule. 3 , 4 This protein, also known as RBM39, HCC1, Caperα, FSAP59 and RNPC2, was found to be distributed in a very speckled network within the nucleus and to colocalize with SC35 and uridine‐rich small nuclear RNA.…”
Section: Introductionmentioning
confidence: 99%
“…RNA‐binding motif (RBM) proteins are members of the family of RNA‐binding proteins (RBPs), which are present in all organisms and can bind single‐ or double‐stranded RNA and play important roles as post‐transcriptional regulators in regulating RNA metabolism and gene expression 2 . By binding RNA, RBPs aggregate in ribonucleoprotein complexes that determine the destiny and function of almost every cellular RNA molecule 3,4 .…”
Section: Introductionmentioning
confidence: 99%